2021
DOI: 10.1021/acs.est.0c06974
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Particulate Matter Sizes and Chemical Constituents with Blood Lipids: A Panel Study in Guangzhou, China

Abstract: Existing evidence is scarce concerning the various effects of different PM sizes and chemical constituents on blood lipids. A panel study that involved 88 healthy college students with five repeated measurements (440 blood samples in total) was performed. We measured mass concentrations of particulate matter with diameters ≤ 2.5 μm (PM2.5), ≤1.0 μm (PM1.0), and ≤0.5 μm (PM0.5) as well as number concentrations of particulate matter with diameters ≤ 0.2 μm (PN0.2) and ≤0.1 μm (PN0.1). We applied linear mixed-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 60 publications
3
14
0
Order By: Relevance
“…Ni exposure was also associated with decreased diastolic blood pressure [ 25 ]. In a study of 88 healthy students, higher concentrations of Ni in PM2.5 components were associated with higher HDL-C [ 51 ], which was consistent with our first sensitivity analysis (model 3). However, that study had a small sample size and did not focus on other blood lipid profiles.…”
Section: Discussionsupporting
confidence: 88%
“…Ni exposure was also associated with decreased diastolic blood pressure [ 25 ]. In a study of 88 healthy students, higher concentrations of Ni in PM2.5 components were associated with higher HDL-C [ 51 ], which was consistent with our first sensitivity analysis (model 3). However, that study had a small sample size and did not focus on other blood lipid profiles.…”
Section: Discussionsupporting
confidence: 88%
“…Recent evidence from time-series or panel studies conducted in megacities in China indicated that short-term exposure to UFPs was associated with a series of cardiopulmonary diseases or their biomarkers. 129 , 130 , 131 , 132 , 133 Some studies in China further indicated that the detrimental effects of UFPs were independent of other air pollutants 132 and stronger than larger particles. 132 , 133 The WHO provided a qualitative statement of UFPs in 2021 for the first time, but did not conclude a particular AQG for UFPs due to insufficient epidemiological evidence.…”
Section: Epidemiological Evidence On Health Impacts Of Particulates I...mentioning
confidence: 99%
“…Panel-based study designs are considered an effective method to investigate the associations between and health outcomes ( Feng et al. 2020 ; He et al. 2021 ; Sarnat et al.…”
Section: Discussionmentioning
confidence: 99%